Cell Surface and Adherence Properties of Indonesian Indigenous Lactic Acid Bacteria as Probiotic Candidate - Leksono, Benediktus Yudo; Purwijantiningsih, Ekawati; Wibisono, Gracia Irene Benaya (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2024)
Adherence to intestinal mucosa is one of the crucial probiotic traits. This ability varied among strains. This study aims to evaluate the cell surface properties and adherence potential of Indonesian Indigenous LAB. The adherence potential was evaluated using auto- aggregation, coaggregation against Salmonella, cell hydrophobicity, and adherence to stainless-steel surface. All strains classified as having medium high aggregation (>90%) after 24 h of incubation and can coaggregate with Salmonella (58-92%). Among all strains, Levilactobacillus brevis AB3 showed the highest hydrophobicity (36%) and adhesion to stainless steel (6.37 log CFU/mL). Current findings suggest that Indonesian Indigenous LAB, especially L. brevis AB3, possessed an adherence property and has a potential to be developed into probiotic bacteria.